Analyze Performance of Torque Boosting Device - Ramli, Muhammad Nurshafiq (IRC, 2016)
This project focus on research and analysis torque output from chain drives system of motorcycles. The rear sprocket of motorcycle chain drives system play a crucial role in generating torque. Current motorcycle sprocket systems are based on 36-teeth sprocket which is suitable for a regular street bike but unsuitable for hilly terrain and for carrying heavy payload. Farmers and villagers living in hilly terrain mainly use their motorcycle for their daily chores and have to travel steep road while carrying heavy payload such as farm produce, fertilizer and pesticides in daily routine.